Non-functional cervical paraganglioma in an adult: A case report (Indian Journal of Case Reports, 2019)
Paragangliomas are rare neuroendocrine tumors. The most common site is the adrenals cervical region. Cervical paragangliomas are divided into carotid body and vagus types. Here, we report the case of a non-functional cervical paraganglioma in a 78-yearold male came with complaints of swelling in the left side of the neck for 2 years. On imaging, guided core needle biopsy showed eosinophilic cells with vacuolated nuclei and some inclusion bodies which suggested a possible clear cell tumor, neuroendocrine tumor or a paraganglioma. Complete surgical excision was done under general anesthesia, postoperative histopathology and immunohistochemistry markers (S100, Synaptophysin, and Ki67) suggested of paraganglioma.